2015
DOI: 10.1186/s13075-015-0575-8
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex cytokine analysis of dermal interstitial blister fluid defines local disease mechanisms in systemic sclerosis

Abstract: IntroductionClinical diversity in systemic sclerosis (SSc) reflects multifaceted pathogenesis and the effect of key growth factors or cytokines operating within a disease-specific microenvironment. Dermal interstitial fluid sampling offers the potential to examine local mechanisms and identify proteins expressed within lesional tissue. We used multiplex cytokine analysis to profile the inflammatory and immune activity in the lesions of SSc patients.MethodsDermal interstitial fluid sample from the involved fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 16 publications
1
20
0
2
Order By: Relevance
“…PDGF-A is overexpressed in SSc lesions (Yamakage et al, 1992) and increased expression of PDGFRα and PDGFRβ on spindle cells correlates with collagen deposition in SSc biopsies (Daoussis et al, 2012). Increased PDGF-A has also been reported in the dermal interstitial blister fluid of SSc patients (Clark et al, 2015). In addition, agonistic anti-PDGFRα autoantibodies have been detected in the serum of SSc patients (Moroncini et al, 2015).…”
Section: Introductionmentioning
confidence: 89%
“…PDGF-A is overexpressed in SSc lesions (Yamakage et al, 1992) and increased expression of PDGFRα and PDGFRβ on spindle cells correlates with collagen deposition in SSc biopsies (Daoussis et al, 2012). Increased PDGF-A has also been reported in the dermal interstitial blister fluid of SSc patients (Clark et al, 2015). In addition, agonistic anti-PDGFRα autoantibodies have been detected in the serum of SSc patients (Moroncini et al, 2015).…”
Section: Introductionmentioning
confidence: 89%
“…In the articles included in this review, the negative pressure was between 200 and 400 mmHg, the suction cups ranged in size from 5 to 15 mm and the time needed for the formation of the blisters was mostly 2-3 h. Warming was sometimes added to aid blister formation. For the quantification of the protein levels of IL-1α and/or IL-1RA, the majority used EIA/ ELISA (n = 10) (43-52) and the remaining used multiplex arrays (53)(54)(55)(56)(57). All studies but 2 analysed additional cytokines and chemokines, albeit many reported that not all could be detected (43-45, 51, 52, 54, 55).…”
Section: Skin Suction Blisteringmentioning
confidence: 99%
“…Возникло предположение об ассоциации этих субтипов с ответом на иммуносупрессивную терапию [49]. Недавнее изучение интерстициальной жидкости из пораженной кожи боль-ных ССД с помощью мультиплексного анализа показало существенные различия в локальной концентрации воспа-лительных и профиброзных белков [50]. Это исследование подтвердило существование субпопуляций больных с раз-ным профилем доминирующих цитокинов, а также выяви-ло подгруппу больных с высокими уровнями ИЛ6 в коже (без повышения в циркуляции), что, по мнению авторов, может предполагать перспективность применения таргет-ной терапии против ИЛ6 в этой подгруппе больных.…”
Section: Adam17unclassified
“…Средний возраст больных составил 58 (46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61) лет. Исходно 73% больных получали низкие дозы ГК (≤10 мг/сут в пересчете на преднизолон) и 57% -метотре-ксат.…”
Section: Adam17unclassified